PSX-13 The University of Missouri DVM-MS Dual Program in Bovine Reproduction. (7th December 2018) - Patterson, D; Locke, J; Knickmeyer, E; Bonacker, R; Thomas, J; Smith, M; Poock, S
Abstract: The University of Missouri dual DVM-MS program provides further training and expertise in the area of beef cattle reproduction to veterinary students planning to enter a food animal practice. Veterinarians play an important role in reproductive management of dairy herds across the U.S., however, in many cases, practitioners have had limited involvement in reproductive management of beef herds. The reasons for this vary, however there are numerous ways practitioners are now able to become more actively involved in reproductive management of our nation's beef herds. The Missouri Show-Me-Select Replacement Heifer Program changed the way veterinarians assist beef producers with heifer development programs in areas related to reproductive health and management. Veterinarians involved in the Show-Me-Select Program are more actively involved with participating farms, and see increased demand for more specialized services, including ultrasound for early pregnancy diagnosis, fetal aging and fetal sexing. In addition, some practitioners offer expanded services that include estrus synchronization and AI. As value-added programs gain momentum in the industry, the differentiation of AI-sired from natural service sired calves, and the determination of fetal sex will become more common and perhaps even expected. Furthermore, protocols that facilitate use of fixed-time AI have influenced the adoption of new reproductive technologies in beef herds. These technologies accelerate the rate of genetic improvement and change the way that beef producers embrace technology adoption. Students that have been or that are currently enrolled in the dual program gain extensive experience in the areas previously listed, and develop a sound appreciation and working understanding of the scientific method and how to conduct meaningful research. Additionally, these students develop critical relationships with veterinarians, the AI industry, and the major pharmaceutical companies. The program has been a win-win for students, faculty, the colleges involved, and the beef industry of Missouri.